THE INFLUENCE OF DIGITAL BANKING AND RISK FACTORS ON PERFORMANCE BANKING COMPANY (CASE STUDY OF A REGISTERED BANK ON THE INDONESIA STOCK EXCHANGE) - Sara Nadia; Rico Nur Ilham; Sahnaya Khairunnisa; Hasatiru Auwa; Nadia Shalaty (Universitas Efarina, 2022)
The aim of this research is to determine and analyze the influence of DigitalBanking and Risk Factors on Banking Company Performance. The sample in thisresearch was banking companies listed on the Indonesia Stock Exchange in 2017-2022, which were taken using a non-probability sampling method using a purposivesampling technique. This resulted in a sample of 22 companies. The type of researchused is quantitative. The data analysis technique uses multiple linear regressiontechniques with the help of e-views software. The test results show that the digitalbanking variables, credit risk, inflation and economic growth simultaneouslyinfluence the financial performance of banks listed on the Indonesia StockExchange for the 2017-2022 period. Meanwhile, partially, the digital bankingvariable, credit risk has an influence on the financial performance of banks. listedon the Indonesian Stock Exchange, while inflation and economic growth variableshave no influence on the financial performance of banks listed on the IndonesianStock Exchange.